Upaya dalam Meningkatkan Literasi, Numerasi, dan Adaptasi Teknologi Siswa melalui Program Kampus Mengajar 4 di SMP Widya Gama Mojosari - Febianti Putri Noor Wahyuni; Didiek Tranggono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Teaching Campus Program Batch 4 is a continuation of the previous Batch Teaching Campus Programs, Batch 1, 2, and 3. This program is part of the Merdeka Learning Kampas Merdeka (MBKM) Policy issued by the Ministry of Education and Culture of the Republic. (Kemendikbud RI) of Indonesia. The existence of the Teaching Campus Program aims to help restore the quality of education after the Covid-19 pandemic and coordinate education across Indonesia so that there are no gaps between schools. Additionally, student literacy and numeracy have suffered setbacks due to lack of optimal education, lack of facilities, and lack of independent curriculum understanding during the Covid-19 pandemic. Nearly two years of his doing all activities at home, including home learning, in Indonesia. Home learning is enough to prevent transmission of the Covid-19 virus, but it has no effect on children's learning. This also happened to her Widya Gama middle school student who experienced declining literacy and numeracy. Dedicated methods are collaborative methods in which the research used is descriptive and qualitative. For five months, students teaching on campus undertook multiple work programs to improve their literacy and numeracy skills. Of course, there were various obstacles in the implementation, but we managed to keep the program running for five months and on schedule.